The effect of leadership style and job motivation on the performance of teachers - Ramsiah Hiranah; Happy Fitria; Achmad Wahidy (JPGI (Jurnal Penelitian Guru Indonesia), 2021)
The main objective of this study is to define and explain the impact on teacher performance of the leadership style of the head of the Madrasah and job motivation simultaneously. Quantitative analysis is this form of study performed in this study. Techniques for qualitative data collection, questionnaires and documentation..“ Using different linear regression models, it was analyzed. With the help of the version 21 SPSS program. A saturated sampling technique was used in this analysis, where all 49 respondents were tested. From the following conclusions, the findings of data processing and interpretation are drawn: The principal's leadership style has a positive and important effect on the performance of teachers. Motivation for work has a positive and meaningful influence on the success of teachers. At the same time, the leadership style of madrasah principals and job motivation have a profound influence on teacher performance.